Association between adolescent pregnancy and hyperbilirubinemia and low weight at birth: retrospective cohorte in a hospital in Perú, 2015-2016 - Hernández Maldonado, Cindy (2019)
Introduction. Adolescent pregnancy in Peru is a public health problem that has high prevalence in regions such as Ica, and is considered as a cause of certain adverse outcomes to the health of the newborn as low weight and hyperbilirubinemia. Methods. A retrospective cohort was designed consisting of adolescent pregnant women between 13 and 19 years of age, which were divided into two groups: group 1 (<18 years of age) and group 2 (≥18 years of age). Results. A total of 481 adolescent pregnant women were evaluated, of which group 1 represented 65,3%. Newborns with low weight and hyperbilirubinemia were found in 3,3% and 18,9%, respectively. The bivariate analysis showed significant differences (p<0,001) between the median gestational age among mothers with newborns with normal weight and low weight, as well as in relation to the type of delivery (cesarean and normal). Regarding hyperbilirubinemia, both bivariate and multivariate analyzes showed no significant differences. The Cox regression showed that adolescent pregnant women in group 1 had almost 8 times more risk (HR: 7,95, p<0,05) of having a newborn with low weight compared to the pregnant women in group 2. Conclusion. Adolescent pregnancy is associated with low birth weight, but not with neonatal hyperbilirubinemia.